Perceptions of Disability and Special Education Services: The Perspectives of Korean-American Parents of Children with Disabilities - Choi, Nari; Ostendorf, Raymond (Journal of the American Academy of Special Education Professionals, 2015)
Parents’ perception of disabilities and special education services can impact the way they interact with professionals providing services for their children with disabilities. In addition, the cultural background of parents plays an important role in their perception of disabilities, as well as how they communicate with professionals. Thus, it is essential to examine how cultural contexts influence Korean-American parents’ viewpoint of disability and their perception of special education services in order to improve practice when providing appropriate special education services. This paper provides a review of the literature about the perceptions of Korean-American parents of children with special needs in terms of disability and special education services. The difficulties these children encounter in receiving proper special education services will also be discussed. Suggestions for better understanding cultural issues and providing appropriate support for Korean-American children with disabilities will be offered. Lastly, implication for practitioners will be discussed.